Pengembangan Kemampuan Menulis Melalui Teknik Copy The Master - Resyi Abdul Gani; Rina Rosdiana (FKIP UNIVERSITAS PAKUAN, 2016)
To find out the students’ learning outcome and activity in the learning process, an effective learning technique needs to be chosen. Therefore, the learning process development is done using the technique of copy the master to the fifth semester students in the Indonesian Language and Literature Study Program. The data gained was analyzed descriptively with qualitative approach. The learning outcome on expositoric descriptive shows “good” result (75.45 %). On impressionistic descriptive essay, the average score was 79.13 %. Besides that, the data showing that the students used imagining is 100 %. The percentage of imagining use from the strongest to the weakest is sight (100 %), Hearing (50%), sensing (50%), tester (65%), smelling (50%), it also shows the ability to write a description that has used strengthening language. Another thing is the consistence between the writing and the model chosen that are structured and relevant way. This learning outcome is correlated with the data gained from the questionnaires and interviews. Students’ positive response in the class shows that 100% of the students were interested, understood easily, motivated, promoted cooperation, responsible, and independent. The media used was interesting and the learning process was exciting. Besides that, 95.65% of the material is understandable and correlates with the evaluation. The worksheet is stimulating (91.30%). It shows that the learning process using copy the master technique is more exciting, easy to understand, more effective, and memorable.